An alternative model of pre-hospital care for 999 patients who require non-emergency medical assistance. Issue 2 (7th August 2017) - Blodgett, Joanna M.; Robertson, Duncan; Ratcliffe, David; Rockwood, Kenneth
Abstract : Purpose: With the increasing demand on ambulance services, paramedics are tasked to arrange as much out of hospital care as possible, to develop integrated systems of care and work with hundreds of different providers – all in the 15 minutes allocated for assessment. A UK ambulance trust is navigating and leading much of this work as one of the first trusts to implement a general practitioner referral policy as an alternate to direct conveyance. The paper aims to discuss this issue. Design/methodology/approach: Here the authors discuss the referral scheme, examine the limited evidence available and discuss what is needed to influence prospective success of implementing this scheme in other trusts. Findings: Limited evidence for these schemes are described, however there is a clear gap in critical appraisal and methodologically rigorous evidence needed to implement these schemes in other ambulance schemes. Originality/value: In order to facilitate collaboration of healthcare services and to minimize the burden of increasing numbers of patients, communication and discussion of alternate routes of care is crucial. This viewpoint piece is one of the first to emphasize the potential benefits of such schemes.